THE ROLES OF DORMITORY SUPERVISORS AT AL-AZHAR SOLO BARU ISLAMIC BOARDING SCHOOL IN SHAPING STUDENT CHARACTER - Noor Cahyani Purbosari Susilo; M. Darojat Ariyanto; Nurul Latifatul Inayati; Mohammad Zakki Azani (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
This study aims to determine the role of the supervisor dormitory (Musyrifah) in shaping the character of students in the Al-Azhar Solo Baru student dormitory and its solutions. This study describes Musyrifah's persistence in shaping the character of students, including religious, honest, disciplined, responsible, and independent characters. The methods used to obtain data in this research are observation, interviews, and documentation. The results of this study prove that the problem of Musyrifah in shaping the character of students is that students are still less disciplined and cannot be separated from several student factors, namely external factors and internal factors. This study found several roles of Musyrifah, including by always giving directions and admonitions to students, being a good role model for them, also very influencing them, and being open to each other in communicating. As well as cooperation between Musyrifah, parents, and the school to always support students when they are in the school environment and outside the school.